Ensayos de espuma con agua del Río Paraná y H2S - Strehar, Norberto Rodolfo; Aprile, Roberto; Molinari, Marcelo Antonio (Comisión Nacional de Energía Atómica; Argentina, 1979)
Fil: Strehar, Norberto Rodolfo Comisión Nacional de Energía Atómica; Argentina